A Generalized Theorem for Joint-Ventures and Licensing Negotiations - Contractor, Farok J. (Journal of International Business Studies, 1985)
Traditional theory has viewed direct investment, licensing and trade mainly as foreign market-entry alternatives. However, a growing number of overseas ventures are being formed as a mix of the 3 methods, where a joint venture partner may be compensated by a package involving some return on equity investment, plus royalties, plus margins on components or finished product traded with the joint venture corporation. This paper presents an algebraic model for the negotiations position of each partner in a prospective venture. The trade-offs between the 3 compensation types are complex as they involve non-zero-sum games. The methodology is extended to enable a host government to calculate for each alternative arrangement, the foreign exchange cost, tax revenues, or other national costs and benefits. The model makes some unconventional recommendations for corporate strategy and government policy.